Neonatal and maternal upregulation of antileukoproteinase in horses - Holmes, Camille M.; Babasyan, Susanna; Wagner, Bettina (Frontiers in Immunology, 2024)
The end of gestation, ensuing parturition, and the neonatal period represent highly dynamic phases for immunological changes in both mother and offspring. The regulation of innate immune cells at the maternal-fetal interface during late-term pregnancy, after birth, and during microbial colonization of the neonatal gut and other mucosal surfaces, is crucial for controlling inflammation and maintaining homeostasis. Innate immune cells and mucosal epithelial cells express antileukoproteinase (SLPI), which has anti-inflammatory and anti-protease activity that can regulate cellular activation. Here, we developed new monoclonal antibodies (mAbs) to characterize SLPI for the first time in horses and used them to quantify SLPI concentrations in a cohort of mares and their foals during this crucial stage. First, we defined the cell types producing SLPI in peripheral blood by flow cytometry, highlighting the neutrophils and a subset of the CD14 + monocytes as SLPI secreting immune cells. A fluorescent bead-based assay was developed with the new SLPI mAbs and used to establish baseline concentrations for secreted SLPI in serum and secretion samples from mucosal surfaces, including saliva, nasal secretion, colostrum, and milk. This demonstrated constitutive secretion of SLPI in a variety of equine tissues, including high colostrum concentrations. Using immunofluorescence, we identified production of SLPI in mucosal tissue. Finally, longitudinal sampling of clinically healthy mares and foals allowed monitoring of serum SLPI concentrations. In neonates and postpartum mares, SLPI peaked on the day of parturition, with mares returning to the adult normal within a week and foals maintaining significantly higher SLPI secretion until three months of age. This demonstrated a physiological systemic change in SLPI in both mares and their foals, particularly at the time around birth, likely contributing to the regulation of innate immune responses during this critical period.